Highly accelerated free‐breathing real‐time phase contrast cardiovascular MRI via complex‐difference deep learning. Issue 2 (15th March 2021) - Haji‐Valizadeh, Hassan; Guo, Rui; Kucukseymen, Selcuk; Paskavitz, Amanda; Cai, Xiaoying; Rodriguez, Jennifer; Pierce, Patrick; Goddu, Beth; Kim, Daniel; Manning, Warren; Nezafat, Reza
Abstract : Purpose: To develop and evaluate a real‐time phase contrast (PC) MRI protocol via complex‐difference deep learning (DL) framework. Methods: DL used two 3D U‐nets to separately filter aliasing artifact from radial real‐time velocity‐compensated and complex‐difference images. U‐nets were trained with synthetic real‐time PC generated from electrocardiograph (ECG) ‐gated, breath‐hold, segmented PC (ECG‐gated segmented PC) acquired at the ascending aorta of 510 patients. In 21 patients, free‐breathing, ungated real‐time (acceleration rate = 28.8) and ECG‐gated segmented (acceleration rate = 2) PC were prospectively acquired at the ascending aorta. Hemodynamic parameters (cardiac output [CO], stroke volume [SV], and mean velocity at peak systole [peak mean velocity]) were measured for ECG‐gated segmented and DL‐filtered synthetic real‐time PC and compared using Bland‐Altman and linear regression analyses. Additionally, hemodynamic parameters were quantified from DL‐filtered, compressed‐sensing (CS) ‐reconstructed, and gridding reconstructed prospective real‐time PC and compared to ECG‐gated segmented PC. Results: Synthetic real‐time PC with DL showed strong correlation (R > 0.98) and good agreement with ECG‐gated segmented PC for quantified hemodynamic parameters (mean‐difference: CO = −0.3 L/min, SV = −4.3 mL, peak mean velocity = −2.3 cm/s). On average, DL required 0.39 s/frame to filter prospective real‐time PC, which was 4.6‐fold faster than CS. Compared to CS, DL showed superior correlation, tighter limits of agreement (LOAs), better bias for peak mean velocity, and worse bias for CO and SV. Compared to gridding, DL showed similar correlation, tighter LOAs for CO and SV, similar bias for CO, and worse bias for SV and peak mean velocity. Conclusion: The complex‐difference DL framework accelerated real‐time PC‐MRI by nearly 28‐fold, enabling rapid free‐running real‐time assessment of flow hemodynamics.